2008
DOI: 10.1016/j.vetmic.2007.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of positive selection for both F18+ Escherichia coli and stress resistant pigs opens new perspectives for pig breeding

Abstract: F18+ Escherichia coli infections causing post-weaning diarrhoea and/or oedema disease are a major cause of economic losses in pig industry. To date, no preventive strategy can protect pigs from F18 + E. coli infections. One of the most attractive approaches to eliminate F18 + E. coli infections is the selection for pigs that are resistant to F18 + E. coli infections. However, this strategy was not believed to be favourable because of reports of genetic association with the stress-susceptibility gene in the Swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…We herein found very low r 2 values between the two loci in Duroc, Landrace, and Large White pigs (Table 3). This result is consistent with the report by Coddens et al (2008), allowing the possibility of combined selection for both F18 and stress-resistant pigs. …”
Section: Ryr1supporting
confidence: 93%
See 2 more Smart Citations
“…We herein found very low r 2 values between the two loci in Duroc, Landrace, and Large White pigs (Table 3). This result is consistent with the report by Coddens et al (2008), allowing the possibility of combined selection for both F18 and stress-resistant pigs. …”
Section: Ryr1supporting
confidence: 93%
“…Meijerink et al (1997) reported strong linkage disequilibrium between the two loci by showing a 93% association between FUT1 A (favourable) and RYR1 T (unfavourable) alleles in Swiss Landrace pigs. In contrast, no linkage disequilibrium was found between the FUT1 and RYR1 loci in a Belgium pig population (Coddens et al, 2008). We herein found very low r 2 values between the two loci in Duroc, Landrace, and Large White pigs (Table 3).…”
Section: Ryr1contrasting
confidence: 62%
See 1 more Smart Citation
“…Because the most common adhesion factor by which EDEC bind to the enterocytes in the gut are the F18 fimbriae [1] geneticists have been trying to breed a F18-resistant pig for some years [7]. This may be an effective method to face the disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to these earlier findings, it has recently been reported that there is no association between the F18 + E. coli resistance allele and the stress-susceptibility allele in the Belgian pig population. Consequently, selection for breeding pigs with genetic resistance to F18 + E. coli infections can be considered (Coddens et al 2008). Since there is no available commercial vaccine against F18 + E. coli, this protective strategy against F18 + E. coli infections has the potential to be of great economical importance for the pig industry.…”
Section: K88 Fimbriaementioning
confidence: 99%